2008
DOI: 10.1186/1465-9921-9-53
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke worsens lung inflammation and impairs resolution of influenza infection in mice

Abstract: Background: Cigarette smoke has both pro-inflammatory and immunosuppressive effects. Both active and passive cigarette smoke exposure are linked to an increased incidence and severity of respiratory virus infections, but underlying mechanisms are not well defined. We hypothesized, based on prior gene expression profiling studies, that upregulation of pro-inflammatory mediators by short term smoke exposure would be protective against a subsequent influenza infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 51 publications
10
140
0
Order By: Relevance
“…During an influenza infection, IP-10 is released from NECs to attract lymphocytes and T cells to the site of infection (37). Smoke-exposed mice infected with influenza have suppressed levels of whole-lung IP-10 mRNA, with modified profiles of CD4/CD8 T cells in their bronchoalveolar lavage fluid and draining lymph nodes (38). Data from our own laboratory showed that smokers inoculated with live, attenuated influenza virus (LAIV) have reduced concentrations of IP-10 in nasal lavage fluid compared with nonsmoker control samples (T.L.…”
Section: Discussionmentioning
confidence: 99%
“…During an influenza infection, IP-10 is released from NECs to attract lymphocytes and T cells to the site of infection (37). Smoke-exposed mice infected with influenza have suppressed levels of whole-lung IP-10 mRNA, with modified profiles of CD4/CD8 T cells in their bronchoalveolar lavage fluid and draining lymph nodes (38). Data from our own laboratory showed that smokers inoculated with live, attenuated influenza virus (LAIV) have reduced concentrations of IP-10 in nasal lavage fluid compared with nonsmoker control samples (T.L.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cervical immune cell counts [128], smoke constituents found in cervical mucus [129] Immune system Impaired function of leucocytes [124,130] Alterations in lymphocyte subpopulations in CD4 and CD8 cells [131] Depressed cytotoxic activity of natural killer cells [132] Decreased levels of immunoglobulins [133] Increased levels of inflammatory mediators [134] Enhanced oxidative stress [135] The effects of environmental tobacco smoke (ETS) exposure…”
Section: Periodontal Tissuesmentioning
confidence: 99%
“…Increased numbers of neutrophils and macrophages as well as proinflammatory cytokines are found within the airway after either acute or chronic cigarette smoke exposure (10)(11)(12). Several groups showed that exposure to cigarette smoke increases airway inflammation and worsens outcomes in influenza-infected mice (13,14). Furthermore, exposure to cigarette smoke suppressed virally induced Th1 cytokine production and increased viral expression in a mouse model of respiratory syncytial viral infection (15).…”
mentioning
confidence: 99%